Low-dose tamoxifen ameliorates ovariectomy-induced metabolic and immune dysfunction - Heather E. McClurg; Amanda Ferraro; Gina Pham; Itzel Morales-Hernandez; Estefania Valencia-Rincon; Kevin D. Pham; Willard M. Freeman; Jacquelyn A. Gorman; Marisol Castillo-Castrejon (GeroScience, 2026)
The decline in estrogen following menopause is a major driver of metabolic and immune dysfunction in aging females. While hormone replacement therapy improves many of these outcomes, its clinical use remains limited due to concerns regarding estrogen-sensitive malignancies. Tissue-selective estrogen complexes (TSECs), which combine estrogens with selective estrogen receptor modulators (SERMs) such as tamoxifen (TAM), represent a promising strategy to preserve the metabolic and immunological benefits of estrogen while reducing oncogenic risk. However, the systemic effects of TAM under conditions of estrogen deficiency remain incompletely defined. In this study, we investigated the metabolic and immunomodulatory actions of low-dose TAM, alone or in combination with 17β-estradiol (E2), in adult ovariectomized (OVX) female mice. OVX resulted in increased adiposity, hepatic steatosis, glucose intolerance, insulin resistance, immunoglobulin G3 (IgG3) concentration, and systemic inflammation, along with decreased immunoglobulin G1 (IgG1) concentration. E2, TAM, and E2 + TAM each attenuated OVX-induced adipose expansion, adipocyte hypertrophy, and proinflammatory cytokine production. TAM improved insulin sensitivity but did not fully restore glucose tolerance. Transcriptomic analysis of visceral adipose tissue-resident B cells revealed that E2 and E2 + TAM modulate overlapping yet distinct immune-regulatory networks, including suppression of pro-inflammatory signaling, regulation of immune checkpoints, and genes linked to adipose homeostasis. Low-dose TAM emerges as a modulator of estrogen receptor signaling that attenuates multiple features of OVX-induced metabolic and inflammatory dysfunction, though its limited effect on glycemic control highlights the need for tissue-specific evaluation of SERM-based interventions. These findings provide mechanistic insight into endocrine–immune–metabolic interactions and inform strategies to reduce aging-related disease risk in postmenopausal women. Graphical Abstract Created in BioRender ( https://BioRender.com/7ouhlqq ), Castillo M. (2025)